2005
DOI: 10.1073/pnas.0408925102
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the androgen receptor causes oncogenic transformation of the prostate

Abstract: Recent evidence demonstrates that the androgen receptor (AR) continues to influence prostate cancer growth despite medical therapies that reduce circulating androgen ligands to castrate levels and͞or block ligand binding. Whereas the mutation, amplification, overexpression of AR, or cross-talk between AR and other growth factor pathways may explain the failure of androgen ablation therapies in some cases, there is little evidence supporting a causal role between AR and prostate cancer. In this study, we functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
121
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 36 publications
(34 reference statements)
7
121
0
2
Order By: Relevance
“…Although this has been known for many years, only recent work has clearly demonstrated the importance of AR in prostate cancer. This work has shown that mutation of the AR is sufficient for causing prostate cancer development and progression in transgenic mice (Han et al, 2005) and that overexpression of AR converts prostate cancer growth from hormonesensitive to hormone-refractory (Chen et al, 2004). In prostate carcinogenesis, androgens and the AR are important in regulating the proliferation and survival of prostate cells (reviewed by Jenster, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although this has been known for many years, only recent work has clearly demonstrated the importance of AR in prostate cancer. This work has shown that mutation of the AR is sufficient for causing prostate cancer development and progression in transgenic mice (Han et al, 2005) and that overexpression of AR converts prostate cancer growth from hormonesensitive to hormone-refractory (Chen et al, 2004). In prostate carcinogenesis, androgens and the AR are important in regulating the proliferation and survival of prostate cells (reviewed by Jenster, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…AR mutations are frequent in prostate cancer, which often broaden AR ligand specificity and convert AR antagonists to agonists (reviewed in Linja and Visakorpi, 2004). Significantly, a recent study demonstrated that mutation of the AR is sufficient for initiation and progression of prostate cancer in transgenic mice (Han et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The genomic effects of androgens are mediated by the androgen receptor (AR), a nuclear transcription factor that mediates transcriptional responses by targeting sequence-specific DNA regulatory elements. The AR has oncogenic potential, 8 and elevated levels of this protein in clinically localized prostate cancer are predictive of disease progression after radical prostatectomy. 4,9 Much of our understanding of AR function is derived from the study of somatic missense mutations in the AR gene in patients with androgen insensitivity syndrome (inactivating mutations) or in primary, recurrent and metastatic prostate tumors and cell lines.…”
mentioning
confidence: 99%
“…19 Using enforced overexpression of wtAR, AR-T857A (described earlier), or AR-E231G specifically in the prostate of mice, we previously demonstrated the oncogenic capacity of the AR-E231G variant. 8 Although overexpression of wtAR or AR-T857A had no discernable phenotype, mice expressing AR-E231G recapitulated all stages of disease, developing prostatic intraepithelial neoplasia (PIN)-like lesions at 12 weeks of age and advanced prostate cancer with lung metastases by 50 weeks. 8 Many studies have identified and characterized AR target genes in the prostate 20 but in general have not been able to discriminate those that are responsible for AR-mediated tumorigenesis from those that are simply altered due to progression-mediated changes in AR action.…”
mentioning
confidence: 99%
See 1 more Smart Citation